Regulation of Interferon-Stimulated Gene BST2 by a lncRNA Transcribed from a Shared Bidirectional Promoter - Kambara, Hiroto; Gunawardane, Lalith; Zebrowski, Elizabeth; Kostadinova, Lenche; Jobava, Raul; Krokowski, Dawid; Hatzoglou, Maria; Anthony, Donald D.; Valadkhan, Saba (Frontiers in Immunology, 2015)
Recent genome-wide studies have revealed the presence of thousands of long non-protein-coding RNAs (lncRNAs), some of which may play critical roles in the cell. We have previously shown that a large number of lncRNAs show differential expression in response to interferon (IFN)α stimulation in primary human cells. Here, we show that a subset of IFN-induced lncRNAs are positioned in proximity of protein-coding IFN-stimulated genes (ISGs). The majority of gene pairs originated from bidirectional promoters and showed positively correlated expression. We focused our analysis on a pair consisting of the known protein-coding ISG, BST2, and an un-studied putative lncRNA originating from the promoter region of BST2 in a divergent orientation. We showed that this transcript was a multi-exonic, polyadenylated long RNA that lacked protein-coding capacity. BST2 and the lncRNA were both induced in response to IFNα in diverse cell types. The induction of both genes was mediated through the JAK–STAT pathway, suggesting that IFN-stimulated response elements within the shared promoter activated the transcription of both genes. RNAi-mediated knock-down of the lncRNA resulted in down-regulation of BST2, and we could show that this down-regulation occurred at the level of transcription. Forced overexpression of this lncRNA, which we named BST2 IFN-Stimulated Positive Regulator (BISPR), resulted in up-regulation of BST2, indicating that the regulation of expression of BST2 by BISPR is mediated through interactions involving BISPR RNA itself, rather than the impact of its transcription from an adjacent locus. Importantly, upon IFN stimulation, transcriptional activation of BISPR preceded the induction of BST2, suggesting that expression of BISPR facilitated the initiation of transcription in its paired protein-coding gene. The lncRNA-mediated transcriptional regulation described in this study may help govern the expression of additional protein-coding RNAs involved in IFN response and other cellular processes.